William Meredith papers - Meredith, William, 1919-2007.
Correspondence with Robert Lowell and Elizabeth Hardwick relating primarily to poetry and to personal affairs. Also includes correspondence and related material (1978-1979) pertaining to the nomination of poet Robert Earl Hayden to the American Academy and Institute of Arts and Letters. Correspondents include Donald Barthelme, Elizabeth Bishop, Gwendolyn Brooks, John Cheever, John Ciardi, Babette Deutsch, Peter De Vries, Richard Eberhart, Francis Fergusson, Lillian Hellman, Archibald MacLeish, William Maxwell, Howard Nemerov, Walker Percy, Karl Jay Shapiro, William Jay Smith, Wallace Stegner, May Swenson, Kurt Vonnegut, and Robert Penn Warren.
In part, positive photocopies.
Poet.
Collection material in English.
Keywords: Barthelme, Donald -- Correspondence; Bishop, Elizabeth, -- 1911-1979 -- Correspondence; Brooks, Gwendolyn, -- 1917-2000 -- Correspondence; Cheever, John -- Correspondence; Ciardi, John, -- 1916-1986 -- Correspondence; Deutsch, Babette, -- 1895-1982 -- Correspondence; De Vries, Peter, -- 1910-1993 -- Correspondence; Eberhart, Richard, -- 1904-2005 -- Correspondence; Fergusson, Francis -- Correspondence; Hardwick, Elizabeth -- Correspondence; Hayden, Robert, -- 1913-1980.; Hellman, Lillian, -- 1905-1984 -- Correspondence; Lowell, Robert, -- 1917-1977 -- Correspondence; MacLeish, Archibald, -- 1892-1982 -- Correspondence; Maxwell, William, -- 1908-2000 -- Correspondence; Nemerov, Howard -- Correspondence; Percy, Walker, -- 1916-1990 -- Correspondence; Shapiro, Karl Jay, -- 1913-2000 -- Correspondence; Smith, William Jay, -- 1918- -- Correspondence; Stegner, Wallace, -- 1909-1993 -- Correspondence; Swenson, May -- Correspondence; Vonnegut, Kurt -- Correspondence; Warren, Robert Penn, -- 1905-1989 -- Correspondence; American Academy and Institute of Arts and Letters; American poetry; Poetry; Poets